Decoding energy poverty: rural-urban disparities and structural barriers in BRICS countries - Ghosh, Avik (Frontiers in Environmental Economics, 2025)
IntroductionEnergy poverty remains a pressing challenge in emerging economies, particularly in BRICS countries, where significant disparities in clean fuel and electricity access persist across rural and urban populations. Despite global commitments to Sustainable Development Goal 7, the structural determinants of energy poverty including energy availability, efficiency, renewable energy composition, and financial capacity remain poorly understood, especially regarding rural-urban disparities and their distributional effects across different access levels.MethodsThis study employs panel data from 1991 to 2023 for BRICS countries, using access to clean fuels and technologies as the primary measure of energy poverty. The empirical strategy combines three robust econometric approaches: two-way fixed-effects models to control for unobserved heterogeneity, instrumental variable techniques to address endogeneity concerns, and quantile regression to examine distributional effects across deciles of clean fuel access. Key determinants analyzed include energy imports, GDP per unit of energy use (efficiency proxy), and per capita net national income (financial capacity proxy), alongside comprehensive control variables.ResultsThe analysis reveals significant rural-urban disparities in energy poverty determinants. Energy imports positively influence urban clean fuel access but show limited impact in rural areas due to infrastructure constraints. Financial capacity demonstrates stronger effects in rural contexts across all quantiles, with coefficients of 0.0037 (p < 0.01) compared to urban areas. Energy efficiency improvements benefit urban populations, particularly at higher deciles, but have minimal impact on underserved rural communities. Quantile regression results highlight heterogeneous effects, with energy availability becoming increasingly influential at higher access levels while financial capacity remains consistently significant across all quantiles.DiscussionFindings imply that availability-side gains alone are insufficient to close rural gaps without last-mile distribution and affordability support. Policy should combine decentralized renewables and clean-cooking delivery in rural areas, targeted income support, and urban efficiency standards with tariff designs that incentivise fuel-switching. Sequencing should be context-specific, aligning infrastructure rollout with household capacity to pay, to accelerate progress toward SDG 7.